Pancasila in a National Curriculum: Political Education or Indoctrination? - Wicaksana, Ibnu Andy (PCD Journal, 2023)
This article examines the operation of Pancasila, the Indonesian state ideology, in school courses in an Indonesian school in the Netherlands, “Sekolah Indonesia Den Haag” (SIDH). It aims to examine the way Pancasila is taught at SIDH, whether it functions as political education or political indoctrination. The study was conducted using qualitative data analysis, with data from interviews and field observations. The findings show that the way Pancasila is taught at SIDH is a dynamic process consisting of both cultural value and critical engagement to help students understand Indonesia's cultural heritage and instill national identity. The findings also indicate that Pancasila is taught as political education, predominantly relying on rote memorisation and prescribed textbooks, within the context of Dutch liberal cultural values. This leads to identity conflicts among the students. The findings in this study can inform policymaking in education and the formulation of curriculum. For example, to promote a more holistic understanding among students, we can foster critical thinking and open dialogue and encourage interdisciplinary exploration. Investing in teacher professional development may also facilitate meaningful teaching beyond nationalistic symbolism.